Functional reprogramming of human prostate cancer to promote local attraction of effector CD8+ T cells. Issue 12 (16th May 2016) - Muthuswamy, Ravikumar; Corman, John M.; Dahl, Kathryn; Chatta, Gurkamal S.; Kalinski, Pawel
Abstract : BACKGROUND: Local infiltration of CD8 + T cells (CTLs) in tumor lesions predicts overall clinical outcomes and the clinical benefit of cancer patients from immune checkpoint blockade. In the current study, we evaluated local production of different classes of chemokines in prostate cancer lesions, and the feasibility of their modulation to promote selective entry of CTLs into prostate tumors. METHODS: Chemokine expression in prostate cancer lesion was analyzed by TaqMan‐based quantitative PCR, confocal fluorescence microscopy and ELISA. For ex vivo chemokine modulation analysis, prostate tumor explants from patients undergoing primary prostate cancer resections were cultured for 24 hr, in the absence or presence of the combination of poly‐I:C, IFNα, and celecoxib (PAC). The numbers of cells producing defined chemokines in the tissues were analyzed by confocal microscopy. Chemotaxis of effector CD8 + T cells towards the untreated and PAC‐treated tumor explant supernatants were evaluated in a standard in vitro migration assays, using 24 well trans‐well plates. The number of effector cells that migrated was enumerated by flow cytometry. Pearson (r) correlation was used for analyzing correlations between chemokines and immune filtrate, while paired two tailed students t ‐test was used for comparison between treatment groups. RESULTS: Prostate tumors showed uniformly low levels of CTL/NK/Th1‐recruiting chemokines (CCL5, CXCL9, CXCL10) but expressed high levels of chemokines implicated in the attraction of myeloid derived suppressor cells (MDSC) and regulatory T cells (Treg ): CCL2, CCL22, and CXCL12. Strong positive correlations were observed between CXCL9 and CXCL10 and local CD8 expression. Tumor expression levels of CCL2, CCL22, and CXCL12 were correlated with intratumoral expression of MDSC/Treg markers: FOXP3, CD33, and NCF2. Treatment with PAC suppressed intratumoral production of the Treg ‐attractant CCL22 and Treg /MDSC‐attractant, CXCL12, while increasing the production of the CTL attractant, CXCL10. These changes in local chemokine production were accompanied by the reduced ability of the ex vivo‐treated tumors to attract CD4 + FOXP3 + Treg cells, and strongly enhanced attraction of the CD8 + Granzyme B + CTLs. CONCLUSIONS: Our data demonstrate that the chemokine environment in prostate cancer can be reprogrammed to selectively enhance the attraction of type‐1 effector immune cells and reduce local attraction of MDSCs and Tregs . Prostate 76:1095–1105, 2016 . © 2016 Wiley Periodicals, Inc.